A compact Octahedron Dielectric Resonator Antenna For S-Band Wireless Applications - et. al., Bellam Sai Deepak, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The proposed Octahedron design measures a Wide Band incorporated Dielectric Resonator Antenna for S band application. The proposed design is a Octahedron shaped Dielectric Resonating Antenna. DRA is energized by utilizing molded gap. The recreation measure is finished with the assistance of CST Studio suite software. The transmitting structure is works for wideband operation between 2.1GHz to 4.1GHz. The transmission bandwidth is 2GHz and 2.7dB, 3.4dB and 4.6dB of gain observed by the proposed antenna at resonances 2.3GHz, 2.9GHz and 3.7GHz respectively and the Impedance value of the design is 49.8Ohms. The proposed Octahedron Dielectric Resonating radiator has good gain, efficiency, and stable radiation pattern and appropriate for S band application.